Formulation and process optimizations of nano-cosmeceuticals containing purified swiftlet nest. Issue 53 (11th June 2015) - Mohd Taib, Siti Husnaa; Abd Gani, Siti Salwa; Ab Rahman, Mohamad Zaki; Basri, Mahiran; Ismail, Amin; Shamsudin, Rosnah
<x xml:space="preserve">Abstract</x> The usage of purified swiftlet nest in nano-cosmeceuticals and response surface methodology in order to obtain the optimized formulation will be very beneficial and helpful to the swiftlet nest and nano-cosmeceuticals industries worldwide.